Psychological but not motor performance and physiological metrics are influenced in menstrual cycle monitoring during rest and submaximal cycling - Schaffarczyk, M.; Hipp, T.; Fuchs, K.; Reichelt, L.; Rückemann, L.; Gronwald, T. (Medicine & Science in Sports & Exercise, 2026)
Purpose: Despite evidence of phase-dependent performance variations during the menstrual cycle (MC) and potential impairments under oral contraceptives (OC) use, findings remain inconsistent. We studied psycho-physiological and performance fluctuations using a feasible, standardized monitoring battery.